2014
DOI: 10.1186/1475-2867-14-58
|View full text |Cite
|
Sign up to set email alerts
|

Decrease expression of microRNA-744 promotes cell proliferation by targeting c-Myc in human hepatocellular carcinoma

Abstract: BackgroundMicroRNAs (miRNAs) are a large group of post-transcriptional gene regulators that potentially play a critical role in tumorigenesis. Increasing evidences indicate that miR-744 deregulated in numerous human cancers including hepatocellular carcinoma (HCC). However, its role in HCC carcinogenesis remains poorly defined. In this study, we investigated the roles of miR-744 in tumor growth of HCC.MethodsQuantitative reverse-transcription polymerase chain reaction (qRT-PCR) was conducted to detect the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 34 publications
3
45
0
Order By: Relevance
“…For example, Cyclin D1 and E1 are related to the control of G1/S phase in cell cycle progression [45]. C-myc is indispensable for regulating cell growth, proliferation and development [46,47]. C-myc was also reported to be necessary for skin keratinocytes proliferation [27].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cyclin D1 and E1 are related to the control of G1/S phase in cell cycle progression [45]. C-myc is indispensable for regulating cell growth, proliferation and development [46,47]. C-myc was also reported to be necessary for skin keratinocytes proliferation [27].…”
Section: Discussionmentioning
confidence: 99%
“…Under-expression of miR-744-5p was observed in HCC tissues compared with the normal counterparts (Tan et al, 2014;Lin et al, 2014). Furthermore, reduced miR-744-5p exhibited a significant linkage with HCC cases demonstrating multiple tumor nodes or microvascular invasion (Tan et al, 2014).…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…Furthermore, reduced miR-744-5p exhibited a significant linkage with HCC cases demonstrating multiple tumor nodes or microvascular invasion (Tan et al, 2014). In HCC cell lines with low endogenous miR-744-5p expression, introduction of miR-744 mimics reduced HCC growth (Lin et al, 2014). Using luciferase reporter assays, it was demonstrated that miR-744-5p was able to suppress the HCC cell growth by targeting c-Myc (Lin et al, 2014).…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
See 2 more Smart Citations